EFFECT OF LEVEL ZEOLITE FROM DIFFERENT SOURCES IN THE DIETS ON PIGS GROWING-FINISHING PERIOD - Pollung H. Siagian (Institut Teknologi Bandung, 2005)
One of the livestock that has potential to be developed in fulfill the meat requirement is the pig. The excellent traits of the pigs are prolific, high carcas percentage (65-80% of live weight), very efficient in converting feed in to the products. Zeolite is a mine commodity that very potential can be used as mineral source in diets. The minerals has specific characteristic which had high absorption and cation exchange capacity. Zeolite can be used in the diets for increasing feed efficiency. The aim of the research was to study the effect of level zeolite from different sources in the diets on pigs growing-finishing periode. The result showed that the used 6% zeolite level had significant effect on average daily gain and optimal point level used is 4,8%. There were no significant effect of zeolite sources on pig performance. Generally the performance of pigs received feed containing zeolite from L better compared others sources (B,S and N).